2015
DOI: 10.1103/physrevb.92.035105
|View full text |Cite
|
Sign up to set email alerts
|

Probing the electronic properties of graphene on C-face SiC down to single domains by nanoresolved photoelectron spectroscopies

Abstract: Graphene samples with thicknesses ranging from monolayer to few layer graphene grown on the C-face of SiC by Si flux-assisted molecular beam epitaxy were studied to understand their stacking structure. Particular attention was put on determining the size, thickness, spatial distribution, and orientation relative to the SiC of the graphene domains. A complete electronic characterization of the graphene films down to submicrometer grains was obtained by using synchrotron-based conventional and nanoresolved photo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
15
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
3
2
2

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(17 citation statements)
references
References 41 publications
2
15
0
Order By: Relevance
“…The N and W bandwidths are large, which may originate from nearly aligned different grains considering that the beam size is larger than the grain size. The N width is 0.06 Å −1 26 , and the W width is even larger, because its continuous orientation distribution is much wider. To overcome this limitation, we have utilized the state-of-the-art high spatial resolution scanning photoemission k-microscope at the ANTARES beamline.…”
Section: Resultsmentioning
confidence: 97%
See 3 more Smart Citations
“…The N and W bandwidths are large, which may originate from nearly aligned different grains considering that the beam size is larger than the grain size. The N width is 0.06 Å −1 26 , and the W width is even larger, because its continuous orientation distribution is much wider. To overcome this limitation, we have utilized the state-of-the-art high spatial resolution scanning photoemission k-microscope at the ANTARES beamline.…”
Section: Resultsmentioning
confidence: 97%
“…Consequently, using the point mode acquisition, we could measure the band structure within any single N or W grain. After correlated nanoARPES and nano core-level experiments 26 , we showed that N grains only involve AB stacked multilayers (typically 4–6 ML, see supplementary information Fig. S1 ) while W grains mainly include TBG.…”
Section: Resultsmentioning
confidence: 97%
See 2 more Smart Citations
“…It has been extensively found that graphene grown on the C-face hexagonal SiC presents smaller domains with a larger distribution of graphene thickness than on the Si-face [39,[53][54][55][56][57]. Unlike the Si-face, there is no evidence to manifest the existence of a buffer layer on graphene/C-face SiC samples so far, although (2  2), (3  3) surface reconstructions were observed [58].…”
Section: Growth Of Graphene On the C-face Sicmentioning
confidence: 97%